A measure for measure: moderation and the mean in the literature of Spain's Golden Age - Rabone, M (2017)
This thesis presents the first sustained analysis of the reception of the Aristotelian golden mean in early modern Spanish literature. It argues that the critically-neglected ethical credo of moderation was an important part of the classical inheritance on which Golden-Age authors frequently drew, and that despite its famous origins in moral philosophy rather than literature, it was subject to just the same kind of imitative reworking as has long been acknowledged for literary predecessors. The analysis is divided into two sections. The first takes a synoptic view of the period, assessing the transmission of Aristotle's doctrine to the Renaissance and exploring what it meant to the Golden-Age mind. That includes identifying a particular early modern reformulation of the mean, which I argue was an important factor in the popularity of the Icarus and Phaethon myths, as analogues for Aristotle's moral. The body of the thesis then comprises three case studies of the role of moderation in works which span the period’s chronological and generic range: the poetry of Garcilaso; Calderón's 'El médico de su honra'; and Gracián's 'Criticón'. These studies explore three important general trends in the reception of the mean: the association of excess and moderation with particular literary models; the incorporation of the mean into Christian thought; and its parallel existence as non-technical, commonplace wisdom. However, each chapter also constitutes an innovation within its own field, offering a reassessment of Garcilaso's relationship to literary tradition; a re-reading of the characters and plot structure of 'El médico', including the controversial King Pedro; and an analysis of the elusive moral approach behind Gracián's allegorical novel. The mean is thus remarkable for both the breadth and depth of its incorporation into literature, and a focus on its treatment offers substantial new insights into some of the canonical works of the age.